Rat Small Intestinal Mucosal Epithelial Cells Absorb Dietary 1, 3‐Diacylglycerol Via Phosphatidic Acid Pathways. Issue 3 (27th April 2018) - Xu, Tongcheng; Li, Jianpeng; Zou, Jiayong; Qiu, Bin; Liu, Wei; Lin, Xinying; Li, Duo; Liu, Zhenhua; Du, Fangling
Abstract: Compared with triacylglycerol (TAG), dietary 1, 3‐diacylglycerol (1, 3‐DAG) is associated with reduced serum lipid and glucose levels. We investigated the metabolism of 1, 3‐DAG by assaying its intermediate metabolites during digestion and absorption in the rat small intestine. After gavage with TAG emulsion, TAG was digested mainly to 2‐monoacylglycerol (2‐MAG) and unesterified fatty acid (FFA) in the rat small intestinal lumen. 2‐MAG was directly absorbed into the small intestinal epithelial cells and esterified to 1, 2(2, 3)‐DAG, and further esterified to TAG. After gavage with 1, 3‐DAG emulsion, 1, 3‐DAG was digested mainly to 1(3)‐MAG and FFA in the rat small intestinal lumen with subsequent significant increase of 1‐MAG and 1, 3‐DAG concentrations in small intestinal mucosal epithelial cells, and the 2‐MAG, 1, 2(2, 3)‐DAG, and TAG concentrations in mucosal epithelial cells were not significantly different after 1, 3‐DAG than after TAG gavage, suggesting that the metabolic pathway of 1, 3‐DAG is different from that of TAG. In intestinal mucosal epithelial cells, we further assayed enzyme levels and gene expression of proteins in the phosphatidic acid (PtdOH) pathway. The glycerol kinase, phosphatidate phosphatase, and diacylglycerol acyltransferase‐2 expression and the relative expression of mRNA of enzymes were significantly increased in the 1, 3‐DAG group compared with the TAG group, suggesting that TAG synthesis from dietary 1, 3‐DAG was mainly via PtdOH pathways, which may partially account for the effect of dietary DAG on postprandial serum TAG.